Creating Logo, Web Site & Application for CodeX Cybersecurity Company - (:unkn) unknown (My University, 2022)
Η παρούσα εργασία επικεντρώνεται στη δημιουργία εταιρικής ταυτότητας, ιστοσελίδας και στη δημιουργία εφαρμογής για κινητά τηλέφωνα. Συγκεκριμένα, στοχεύει στη δημιουργία ολοκληρωμένων λειτουργικών εργαλείων για λογαριασμό της νεοσύστατης εταιρείας παροχής υπηρεσιών ασφαλείας στο διαδίκτυο, CodeX Cybersecurity Company.

This work focuses on the creation of a corporate identity, a website and the creation of an application for mobile phones. In particular, it aims to create from scratch integrated operational tools on behalf of CodeX Cybersecurity Company, a newly established company providing internet security services.
Keywords: html, css, java, android, γραφιστικός σχεδιασμός, σχεδιασμός ιστοσελίδας, CodeX, εφαρμογή για κινητό,εφαρμογή, κυβερνοασφάλεια, χάκερ, ηθικός χάκερ; html, css, java, android, graphic design, web design, code, CodeX, mobile, application, Cybersecurity, ethical hacking, hacker.